A Bifunctional CdS/MoO2/MoS2 Catalyst Enhances Photocatalytic H2 Evolution and Pyruvic Acid Synthesis. (5th October 2022) - Bie, Chuanbiao; Zhu, Bicheng; Wang, Linxi; Yu, Huogen; Jiang, Chenhui; Chen, Tao; Yu, Jiaguo
Abstract: The best use of photogenerated electrons and holes is crucial to boosting photocatalytic activity. Herein, a bifunctional dual‐cocatalyst‐modified photocatalyst is constructed based on CdS/MoO2 /MoS2 hollow spheres for hydrogen evolution coupled with selective pyruvic acid (PA) production from lactic acid (LA) oxidation. MoS2 and MoO2 are simultaneously obtained from the conversion of CdMoO4 in one step. In a photocatalytic process, the MoS2 and MoO2 function as the reduction and oxidation centers on which photogenerated electrons and holes accumulate and are used for hydrogen evolution reaction (HER) and PA synthesis, respectively. By monitoring the intermediates, a two‐step single‐electron route for PA production is proposed, initiated by the cleavage of the α‐C(sp 3 )−H bond in the LA. The conversion of LA and the selectivity of PA can reach ca . 29 % and 95 % after a five‐hour reaction, respectively. Abstract : Photogenerated electrons and holes in CdS hollow spheres loaded with MoS2 and MoO2 dual cocatalysts are applied to hydrogen evolution and selective pyruvic acid production, respectively. This bifunctional strategy can fully utilize the redox abilities of photogenerated electrons and holes to enhance photocatalytic activity.